2021
DOI: 10.1093/eurheartj/ehab254
|View full text |Cite
|
Sign up to set email alerts
|

Functionally validated SCN5A variants allow interpretation of pathogenicity and prediction of lethal events in Brugada syndrome

Abstract: Aims The prognostic value of genetic variants for predicting lethal arrhythmic events (LAEs) in Brugada syndrome (BrS) remains controversial. We investigated whether the functional curation of SCN5A variations improves prognostic predictability. Methods and results Using a heterologous expression system and whole-cell patch clamping, we functionally characterized 22 variants of unknown significance (VUSs) among 55 SCN5A mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 20 publications
3
33
0
1
Order By: Relevance
“…Importantly, non-LOF SCN5A variation carriers ( n = 15) exhibited no LAEs during the follow-up period. 53 Multivariate analysis demonstrated that only LOF SCN5A mutations and a history of aborted cardiac arrest were significant predictors of LAEs. 53 Rare variations of non-SCN5A BrS-associated genes did not affect LAE-free survival curves.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathmentioning
confidence: 97%
“…Importantly, non-LOF SCN5A variation carriers ( n = 15) exhibited no LAEs during the follow-up period. 53 Multivariate analysis demonstrated that only LOF SCN5A mutations and a history of aborted cardiac arrest were significant predictors of LAEs. 53 Rare variations of non-SCN5A BrS-associated genes did not affect LAE-free survival curves.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathmentioning
confidence: 97%
“…SCN5A gene variants may be important predictors of fatal events in BrS and valuable in risk stratification [ 57 ]. Loss-of-function SCN5A mutations have shown association with prolonged ECG conduction parameters (P wave or QRS durations) and increased occurrence of lethal arrhythmic events compared to the non-loss-of-function SCN5A mutations or SCN5A(−) BrS patients [ 57 ].…”
Section: Diagnostics and Risk Stratificationmentioning
confidence: 99%
“…Extrapolating their patch clamp data has the potential to reduce the total Nav1.5 VUS functional burden by at least 75%. This assay was further validated in a study of 22 Nav1.5 variants showing patch clamp data to be an excellent predictor of pathogenicity and lethal cardiac arrhythmias in Brugada Syndrome ( 63 ).…”
Section: Scn5a/nav15mentioning
confidence: 99%